Rozwiąż równanie: (kx-m) (px - p) = 12x^2 - 46x +20​

Odpowiedź :

Odpowiedź:

lewa strona= kpx²-kpx-mpx+mp= kpx²- ( kp+mp)x +mp

                                                       12 x²-     46     x  +20

...........................................................................................................

kp=12                   kp+mp=46           mp=20

p=12/k                 p(k+m)=46              k≠0       m*(12/k)=20

12m=20k                     3m= 5k

m= 5k/3

......................

p(k+m)=46

12/ k  (k+   5k/3) =46

12+  20k=46

20k=34

k=17/10

...........................

p=12:k= 12*10/17=120/17

................................................

m= 5/3   k=   5/3  *  17/10=17/6

.........................................................

                               

Szczegółowe wyjaśnienie: